2018
DOI: 10.1088/1748-3190/aaeb01
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on acoustic reception pathways in finless porpoise (Neophocaena asiaorientalis sunameri) with insight into an alternative pathway

Abstract: Sound transmission and reception are both vital components to odontocete echolocation and daily life. Here, we combine computed tomography (CT) scanning and Finite Element Modeling to investigate the acoustic propagation of finless porpoise (Neophocaena asiaorientalis sunameri) echolocation pulses. The CT scanning and FEM wave propagation model results support the well-accepted jaw-hearing pathway hypothesis and suggest an additional alternative auditory pathway composed of structures, mandible (lower jaw) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…Using finite element modeling, Cranford et al (2008) identified an additional sound-reception pathway-the so-called "gular pathway"-by which sounds enter the internal mandibular fat through the ventral margin of the mandible; these findings were based on a case study of a Cuvier's beaked whale (Ziphius cavirostris). In addition, sound-reception channels in which the solid mandible may play a significant role were introduced in both the experiments and numerical models (Castellote et al, 2014;Mooney et al, 2008;Mooney et al, 2015;Mooney et al, 2018;Song et al, 2018). These results indicate that the entire head may function as an antenna system for sound reception (Popov et al, 2019).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Using finite element modeling, Cranford et al (2008) identified an additional sound-reception pathway-the so-called "gular pathway"-by which sounds enter the internal mandibular fat through the ventral margin of the mandible; these findings were based on a case study of a Cuvier's beaked whale (Ziphius cavirostris). In addition, sound-reception channels in which the solid mandible may play a significant role were introduced in both the experiments and numerical models (Castellote et al, 2014;Mooney et al, 2008;Mooney et al, 2015;Mooney et al, 2018;Song et al, 2018). These results indicate that the entire head may function as an antenna system for sound reception (Popov et al, 2019).…”
Section: Introductionmentioning
confidence: 85%
“…The sound-transmission and -reception pathways were not located in the same sagittal plane. In previous twodimensional models, these two systems were typically separated into their respective models (Zhang et al, 2017;Song et al, 2018). However, this restricts our understanding of the bio-sonar target-detection capabilities.…”
Section: A Sound Transmission and Receptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, bone heterogeneity, neglected in other similarlyminded numerical studies (e.g. [17,18]) is accounted for in our simulations. While it is impossible (for a number of technical reasons that we discuss) to reproduce Reinwald et al's [2] experiment exactly, our results share all the important features of their data.…”
Section: Introductionmentioning
confidence: 99%